Low-dose CT of paediatric paranasal sinus using an ultra-low tube voltage (70 kVp) combined with the flash technique. Issue 1 (January 2021) - Chi, J.; Ji, Y.-D.; Shen, L.; Yin, S.-N.; Ding, N.; Chen, X.-F.; Xu, D.-F.
Abstract : AIM: To evaluate the radiation dose and diagnostic image quality of low-dose computed tomography (CT) of the paranasal sinus in children, with acquisition at an ultra-low tube voltage (70 kVp) combined with the Flash technique. MATERIALS AND METHODS: Eighty paediatric patients underwent CT of the paranasal sinus and were divided into two groups according to different protocols (group A: 80 kVp protocol with conventional spiral mode [ n= 40] and group B: 70 kVp protocol with Flash scan mode [ n= 40]). For each examination, the CT dose index (CTDIvol), dose–length product (DLP), and effective dose (ED) were estimated. The image noise, signal-to-noise ratio (SNR), and overall subjective diagnostic image quality were also evaluated. RESULTS: For radiation dose, the CTDIvol (mGy), DLP (mGy·cm), and ED (mSv) values of the 70 kVp protocol were significantly lower than those of the 80 kVp protocol (CTDIvol: 1.57±0.009 versus 0.39±0.004 mGy, p <0.001; DLP: 19.88±2.01 versus 6.31±0.52 mGy·cm, p <0.001; ED: 0.079±0.016 versus 0.024±0.005 mSv, p <0.001). Compared with those of the 80-kVp protocol, the image noise increased by 40.7% ( p =0.113), the SNRsoft-tissue decreased by 48.9%, and the SNRbone increased by 10.1% with the 70-kVp protocol ( p =0.176 and 0.227, respectively). There was no significant difference in the overall subjective image quality grades between these two groups ( p =0.15). CONCLUSION: When imaging the paranasal sinus in children, an ultra-low tube voltage (70 kVp) combined with the Flash CT technique can reduce the radiation dose significantly while maintaining diagnostic image quality with clinically acceptable image noise. Highlights: Evaluation of ultra-low tube voltage (70 kVp) combined with Flash scan technique. A new scan protocol could significantly reduce the CT scan dose of children's paranasal sinus. The new scan protocol could produce virtually no artifacts caused by pediatric patient motion. The new scan protocol could maintain image quality for accurate diagnosis at an ultra-low dose level.